ANALISIS PENERAPAN LAPORAN KEUANGAN BERBASIS STANDAR AKUNTANSI KEUANGAN – ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA USAHA MIKRO KECIL MENENGGAH (UMKM) UD. AJIWON POLYBOGA INDONESIA - Izzah Afkarini; Annisah Febriana (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This research aims to examine how effectively the financial reporting adhering to SAK ETAP is utilized by MSME UD. Ajiwon Polyboga Indonesia. SAK ETAP represents an accounting framework tailored specifically for entities that lack significant public accountability and do not prepare general-purpose financial reports for external stakeholders. In the realm of MSMEs, utilizing SAK ETAP is anticipated to improve financial transparency and accountability, while also creating a stronger basis for decision-making by business proprietors and affiliated parties. The methodology adopted for this research is qualitative, using a case study approach, and includes data gathering techniques like interviews with management, direct observation of financial recording and reporting practices, as well as the documentation of prepared financial statements. The results of the study reveal that while UD. Ajiwon Polyboga Indonesia shows commitment to consistently producing financial reports, the application of SAK ETAP principles has not yet fully aligned with the prescribed standards. Several accounts, particularly the balance sheet and income statement preparation, remain simplistic and do not comply with widely accepted accounting norms. The primary challenges hindering the implementation of SAK ETAP involve the management's limited comprehension of accounting standards, alongside a shortage of qualified personnel specialized in accounting. This study concludes that even though there is an acknowledgment of the significance of financial reporting, the adoption of SAK ETAP within MSMEs such as UD. Ajiwon Polyboga Indonesia still encounters various structural and technical hurdles. Consequently, ongoing training facilitated by external entities like local governments, educational institutions, or accounting advisors is essential for MSMEs to enhance the quality of their financial reporting and bolster their business competitiveness.